2015
DOI: 10.1371/journal.pmed.1001788
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Detection of Plasmodium falciparum by Amplification of Multi-Copy Subtelomeric Targets

Abstract: BackgroundPlanning and evaluating malaria control strategies relies on accurate definition of parasite prevalence in the population. A large proportion of asymptomatic parasite infections can only be identified by surveillance with molecular methods, yet these infections also contribute to onward transmission to mosquitoes. The sensitivity of molecular detection by PCR is limited by the abundance of the target sequence in a DNA sample; thus, detection becomes imperfect at low densities. We aimed to increase PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
367
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(384 citation statements)
references
References 73 publications
4
367
0
Order By: Relevance
“…Recent studies in endemic areas have shown that more sensitive detection methods reveal larger reservoirs of asymptomatic P. falciparum infection than previously appreciated [44,45]. Therefore, it is possible that some subjects in this study had parasite densities below the detection limit of our PCR assay.…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies in endemic areas have shown that more sensitive detection methods reveal larger reservoirs of asymptomatic P. falciparum infection than previously appreciated [44,45]. Therefore, it is possible that some subjects in this study had parasite densities below the detection limit of our PCR assay.…”
Section: Discussionmentioning
confidence: 80%
“…This may be due to degradation of nucleic acids that disproportionally affect RNA-based diagnostics 3 or to a limitation in sensitivity regardless of sample handling. Gametocytaemic individuals with sub-PCR infection were also found in a cross-sectional survey in Tanzania using a new ultra-sensitive PCR technique 12 . These findings illustrate that the available diagnostics do not detect all infections that are present in populations and that onward malaria transmission is possible (although with a low probability) from apparently parasite-negative individuals.…”
Section: Discussionmentioning
confidence: 88%
“…The advent of highly sensitive molecular methods that detect parasite DNA or RNA such as polymerase chain reaction (PCR) 12 and quantitative nucleic acid sequence based amplification (QT-NASBA) has highlighted that many infected individuals have parasite densities that are too low to be detected either by microscopy or RDTs 13,14 . However, even these methods do not detect all the infections that are present in infected human hosts 12,15 and they are currently not available as routine field diagnostic tests because they require high-level laboratory facilities for nucleic acid extraction, amplification and detection that are unavailable in many resource-poor endemic settings. Even the most operationally attractive molecular diagnostic available -loop-mediated isothermal amplification For each value of the x-axis we calculate the proportion of each density distribution (from a) that would be detected.…”
Section: S95mentioning
confidence: 99%
See 1 more Smart Citation
“…After confirmation of successful extraction via Qubit fluorescence (Thermo Fisher Scientific, Waltham, MA, USA), quantitative PCR was attempted to detect the P. falciparum LDH (PfLDH) loci (37). Upon amplification of positive controls but failure of experimental samples, the protocol was adjusted to accommodate an increase from the minimum 1 l of DNA to a maximum of 5 l. Following a second amplification failure, we changed assays to the ultrasensitive protocol targeting the var ATS sequence for qualitative detection to confirm the presence of P. falciparum DNA (38).…”
Section: Methodsmentioning
confidence: 99%